PRIMARY SKIN SARCOIDOSIS- FROM THE POINT OF PATHOLOGIST - Božić, Predrag (PONS - medicinski časopis, 2017)
Introduction. Diagnosis of granuloma is a common finding in pathologists practice, especially specific granuloma in particular inflamations. Diseases in which are the granulomas particularly accentuated are tuberculosis and sarcoidosis because of their similarity, and are easily identified in the differential diagnosis. The diagnosis of sarcoidosis is made based on histopathological findings of the affected tissue, but always as a part of clinical picture along with radiographic and laboratory findings. Sarcoidosis is a multisystem disease of unknown etiology, which can affect many organs.Skin is affected in one third of all cases. The principal role of pathologists in the differential diagnosis is to diagnose the presence of granulomas. With distinctive morphology of granuloma the diagnosis of sarcoidosis and tuberculosis is simple. Case report. A female patient is shown in this report, born in 1975. The disease in this patient is manifested with clinical signs of skin changes in a part of the thorax, as well as on the left upper arm. Preoperative diagnostic procedures have been conducted and they were within the normal limits. Both changes were asymptomatic and were resolved with radical surgery. After final histopathological diagnosis, additional differential diagnostic procedures were conducted such as radiology and laboratory tests, but there has been no outcome which indicate attack or changes on other organs. It turned out to be a primary sarcoidosis of skin, and only in places that are surgicaly treated. Conclusion. Findings of sarcoid granuloma in the skin requires a detail examination primarily due to the possible existence of sarcoid changes in other tissues, especially lung tissue. It also excludes this is a tuberculous change and requires adequate therapeutic treatment for the diagnosis of sarcoidosis. Only the occurrence of such a change on the skin, without any other manifestation in the organs, can be primary, and is the only clinical manifestation of the disease. Sarcoidosis, the skin disease, in case shown here, was not the manifestation of systemic disease in multiple organs, nor a secondary phenomenon